2002
DOI: 10.1007/s00468-001-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient dynamics and leaf litter decomposition in a subtropical mangrove forest at Oura Bay, Okinawa, Japan

Abstract: Dynamics of nutrients (carbon, nitrogen and phosphorus) in decomposing leaves was studied using litterbags in a subtropical mangrove dominated by Bruguiera gymnorrhiza (L.) Lamk and Kandelia candel (L.) Druce (Okinawa, Japan). In addition to fresh yellow leaves, degradation of treated leaves (dried at 50°C and 80°C) was also investigated. Comparison was made between species, locations (lower and upper mangroves) and among treatments. Results showed that K. candel leaves with higher initial N concentrations (lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 29 publications
5
45
0
3
Order By: Relevance
“…Most studies on mangrove litter degradation and concomitant nutrient dynamics have hitherto concentrated on differences among: tidal elevations (Twilley et al, 1986(Twilley et al, , 1997Mfilinge et al, 2002), species and seasons (Tam et al, 1990;Twilley et al, 1997;Woitchik et al, 1997;Mfilinge et al, 2002) and litter components (Steinke et al, 1983;Van der Valk and Attiwill, 1984;McKee and Faulkner, 2000). Specific stand management regimes, i.e., regulated exploitation versus excessive extractive pressure which leads to deforestation, and subsequent reforestation in areas where natural regeneration is impeded, do influence nutrient recycling (Ashton et al, 1999), Reforestation has been found to alter site physico-chemical conditions (McKee and Faulkner, 2000;Bosire et al, 2003) and is thus assumed to ultimately restore the functional importance of nutrient fluxes through it among other ecosystem functions.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on mangrove litter degradation and concomitant nutrient dynamics have hitherto concentrated on differences among: tidal elevations (Twilley et al, 1986(Twilley et al, , 1997Mfilinge et al, 2002), species and seasons (Tam et al, 1990;Twilley et al, 1997;Woitchik et al, 1997;Mfilinge et al, 2002) and litter components (Steinke et al, 1983;Van der Valk and Attiwill, 1984;McKee and Faulkner, 2000). Specific stand management regimes, i.e., regulated exploitation versus excessive extractive pressure which leads to deforestation, and subsequent reforestation in areas where natural regeneration is impeded, do influence nutrient recycling (Ashton et al, 1999), Reforestation has been found to alter site physico-chemical conditions (McKee and Faulkner, 2000;Bosire et al, 2003) and is thus assumed to ultimately restore the functional importance of nutrient fluxes through it among other ecosystem functions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an increase in the TOC concentration may be due to the rising con centrations of structural carbonates per plant and as a result of the loss of other constituents (sugars and starches) in the detritus. The remaining, insoluble plant components are then left to decay (Mfilinge et al 2002;Blum et al 1988). …”
Section: Discussion Litter Degradation and Toc And Tn Dynamicsmentioning
confidence: 99%
“…The initial decreasing trend in the TOC concentration over time in seagrass leaves of Posidonia oceanica lasted for seven days (Mateo 1997), while that of mangrove leaves (Bruguiera gymnorrhiza and Kandelia candel) lasted for 17-31 days (Mfilinge et al 2002).Moreover, studies have also shown that, the degradation of plant materials and the concentration of plant microbes were greater in seagrass leaves than in mangrove leaves (Blum et al 1988, Boer 2000, Holmer and Olsen 2002. Therefore, in this study, the initial decreasing trend in the changes at leaf litter TOC concentration over time was due to a rising propor-tion of structural carbonate per dry matter as a result of the loss of other plant components to detritus.…”
Section: Discussion Litter Degradation and Toc And Tn Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various factors controlling rate of decomposition and energy release, such as, the degree and frequency of tidal inundation, soil temperature [17] and moisture [18], and the presence or absence of the litter-consuming fauna within mangrove forest [19][20][21]. Litter decomposition also increases soil fertility [23].…”
Section: Introductionmentioning
confidence: 99%